Quality of Life in Patients with Breast Cancer following Breast Conservation Surgery: A Systematic Review and Meta-Analysis. (31st January 2022) - Li, Yue; Guo, Jianming; Sui, Yuan; Chen, Baihui; Li, Dalin; Jiang, Jiakang
Abstract : To evaluate the health-related quality-of-life (QOL) outcomes in surgical breast cancer survivors who received breast conservation therapy (BCT) compared to mastectomy, we utilized a systematic review to conduct observational studies of QOL in patients with breast cancer following breast conservation therapy from their inception until October 2021. The PubMed, the Cochrane Library, and the Web of Science databases were systematically searched to retrieve the observational studies. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were applied as an effect estimate and calculated using Stata 15 software. Nine studies comprising 2301 patients were included. The results showed that no significant differences compared to mastectomy were detected for global health status (P = 0.971 and P = 0.613 ), physical function (P = 0.099 ), emotional function (P = 0.096 ), cognitive function (P = 0.377 ), social function (P = 0.602 ), sexual functioning (P = 0.072 ), and sexual enjoyment (P = 0.142 ), while role function (P = 0.036 ), body image (P = 0.000 ), and future perspective (P = 0.012 ) showed a significant difference for BCT when compared to mastectomy. When compared to breast reconstruction (BR), the BCT group was inferior at physical function (P = 0.002 ) and cognitive function (P = 0.040 ) but superior at body image (P = 0.001 ). When used the Functional Assessment of Cancer Therapy (FACT) tool, BCT has better results in physical function (P = 0.000 ), emotional function (P = 0.000 ), and social function (P = 0.000 ) than mastectomy. QOL outcomes after BCT were better than mastectomy in body image, future perspective, and role function. BCT may be an acceptable option in the study setting for breast cancer patients who pursue high QOL.